Consumption of avocado and associations with nutrient, food and anthropometric measures in a representative survey of Australians: a secondary analysis of the 2011–2012 National Nutrition and Physical Activity Survey. Issue 5 (14th September 2022) - Guan, Vivienne X.; Neale, Elizabeth P.; Probst, Yasmine C.
Abstract: Avocados are a rich source of nutrients including monounsaturated fats, dietary fibre, potassium and Mg, as well as phytochemicals. However, no epidemiological analysis for the associations between avocado consumption and participant anthropometric measures has been conducted in Australia. The present study aimed to perform a secondary analysis of the 2011–2012 National Nutrition and Physical Activity Survey (NNPAS) to quantify avocado consumption in the Australian population and explore the associations between avocado intakes, consumption of nutrients and food groups based on the Australian Dietary Guidelines and anthropometric measurements. Usual avocado consumption in the 2011–2012, NNPAS was determined using the multiple source method regression model. The relationship between avocado consumption and intakes of key nutrients and food groups and participant weight, BMI and waist circumference were examined using linear regression. Mean avocado intake was 2·56 (95 % CI: 2·37, 2·75) grams per day with 15·9 % of Australians considered to be 'avocado consumers' ( n 21 526 456 population size; n 12 153 observations). Greater consumption (g) of avocados was associated with significantly higher consumption of monounsaturated fats, polyunsaturated fats, dietary fibre, vitamin E, Mg and potassium, as well as 'whole grains', 'vegetables', 'fruit' and 'meat and alternatives' food groups. Greater consumption (g) of avocados was associated with significantly lower consumption of carbohydrates and discretionary foods. When adjusted for covariates, greater consumption of avocados was significantly associated with a lower body weight ( P = 0·034), BMI ( P < 0·001) and waist circumference ( P < 0·001). Avocados may be incorporated into an eating pattern and may be beneficial in weight management.